Phosphorylation via PKC Regulates the Function of the Drosophila Odorant Co-Receptor - Sargsyan, Vardanush; Getahun, Merid N.; Lavista Llanos, Sofia; Olsson, Shannon B.; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2011)
Insect odorant receptors (ORs) have a unique design of heterodimers formed by an olfactory receptor protein and the ion channel Orco. Heterologously expressed insect ORs are activated via an ionotropic and a metabotropic pathway that leads to cAMP production and activates the Orco channel. The contribution of metabotropic signaling to the insect odor response remains to be elucidated. Disruption of the Gq protein signaling cascade reduces the odor response (Kain et al., 2008). We investigated this phenomenon in HEK293 cells expressing Drosophila Orco and found that phospholipase C (PLC) inhibition reduced the sensitivity of Orco to cAMP. A similar effect was seen upon inhibition of protein kinase C (PKC), whereas PKC stimulation activated Orco even in the absence of cAMP. Mutation of the five PKC phosphorylation sites in Orco almost completely eliminated sensitivity to cAMP. To test the impact of PKC activity in vivo we combined single sensillum electrophysiological recordings with microinjection of agents affecting PLC and PKC function and observed an altered response of olfactory sensory neurons (OSNs) to odorant stimulation. Injection of the PLC inhibitor U73122 or the PKC inhibitor Gö6976 into sensilla reduced the OSN response to odor pulses. Conversely, injection of the PKC activators OAG, a diacylglycerol analog, or phorbol myristate acetate (PMA) enhanced the odor response. We conclude that metabotropic pathways affecting the phosphorylation state of Orco regulate OR function and thereby shape the OSN odor response.